(untitled) (Italian Journal of Public Health, 2012)
Background: low back pain (LBP) has been identified as one of the most costly occupational illnesses among the worldwide working population. Objective: this study was designed to assess the prevalence of LBP among Kosovo power plant workers and to examine whether there was a correlation between age/job tenure and LBP. Methods: a cross sectional questionnaire survey was carried out on 391 workers of the Kosovo Energy Corporation. Two hundred and six production workers (Group I) and 185 office workers (Group II) were included in the study. All the subjects were asked about LBP they had experienced in the previous year. Subjects with LBP then answered the questionnaire regarding the severity of LBP and functional disability caused by LBP. The severity of LBP was evaluated with a 10 mm visual analog scale (VAS). The Oswestry low back pain disability questionnaire (OSW) was used to measure functional disability. Results: the prevalence of LBP was higher in Group I than in Group II (83.4%, 61.6%, respectively, p<0.001). The mean VAS and OSW score was higher in Group I than in Group II (p<0,001 vs. 0.016). There was a significant correlation of age (r= 0.249, p<0.01 and r= 0.155, p<0.05), and job tenure (r=0.245, p<0.01 and r=0.190, p<0.05) with VAS and OSW scores in blue collar workers with LBP. However, there was a statistically significant negative correlation found between job tenure and VAS and OSW scores of the office workers with LBP (p<0.05). Conclusions: low back pain occurred at a high rate within this company. This study identified that age and job tenure correlated with the severity and functional disability of LBP among blue collar workers.